National Birds of the World - Toft, Ron (London Bloomsbury, 2014)
More than 90 species of bird have been adopted by countries as symbols of their national identity. [This work] is a unique celebration of the remarkable birds chosen as emblems by nations.
Include Color Illustrations, References and Index.
Keywords: National characteristics -- Birds -- Birds--Symbolic aspects -- Emblems, National